Trends in Sexual Practices of Nepalese Youth over Time 2006-2016 - Shakya, Dhanendra Veer (Tribhuvan University Journal, 2018)
This study attempts to examine trends in incidence of sexual experience, age at first sex, number of life-time sex partners, multiple sex partners in last 12 months, relationship with last sex partner, and use of condom at last sex if last sex partner was other than spouse or non-live-in-partner among Nepalese youth over time 2006-2016. This study has used 2006, 2011 and 2016 Nepal Demographic and Health Survey data files with weighted cases. Data are analyzed using percentage and frequency tables and statistical tests are carried out using binomial logistic and least square regression models not controlling for variables other than survey years. The findings show that incidences of pre-marital sex, multiple sex partners in last 12 months and other than spouse or non-live-in-partner as last (most recent) sex partner are increasing over time.